Impact of the Think-Pair-Share Instructional Strategy on Secondary School Students’ Academic Retention in Chemistry - Franklin Nnanna Ibe (Indonesian Journal of Innovative Teaching and Learning, 2026)
Background: Academic retention in Chemistry remains a persistent challenge in Nigerian secondary schools, particularly in abstract topics such as acids, bases, and acid–base reactions, where conventional lecture methods often limit long-term understanding. Objective: This study examined the effect of the Think–Pair–Share (TPS) instructional strategy on senior secondary school students’ academic retention in Chemistry and determined whether gender influenced retention outcomes. Method: A quasi-experimental design was employed. The population comprised 5,714 SS1 Chemistry students in Anambra State, from whom 192 were selected using stratified and simple random sampling. The Chemistry Retention Test (CRT), validated by experts, served as the data-collection instrument. Reliability was established using the Kuder–Richardson Formula 20, yielding an internal consistency coefficient of 0.81. The mean and standard deviation addressed the research questions, and ANCOVA tested the hypotheses at the 0.05 level. Result: Students taught using TPS demonstrated significantly higher retention scores than those taught through the lecture method. No significant gender difference was found within the TPS group. Conclusion: TPS enhances long-term retention in Chemistry regardless of gender. Contribution: The study provides empirical evidence supporting TPS as an effective strategy for improving retention in secondary school Chemistry.